The Poisson-Topp-Leone Burr Type-X II Model: Various Uncensored Applications for Statistical Modeling and Some Copulas - Abdullah, Murtadha; Mohammed, Wahhab Salim; Farhana , Aqeel Hameed (Statistics, Optimization & Information Computing, 2023)
The Poisson-Topp-Leone Burr type-X II distribution is studied mainly for illustrating its wide applicability under uncensored engineering and medical real-life datasets. The real-life datasets are checked and analyzed for the statistical modeling purpose. The Poisson-Topp-Leone Burr type-X II model is compared with other nine types of Burr type-X II extensions and provided the best results. For modeling the bivariate uncensored engineering and medical real-life datasets, we presented some bivariate version with some useful theoretical results. Those versions are investigated due to certain and common copulas.